2021
DOI: 10.3390/en14030677
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MgO Nanoparticles on Thermo-Physical Properties of LiNO3-NaNO3-KNO3 for Thermal Energy Storage

Abstract: Molten salt LiNO3-NaNO3-KNO3 has been investigated as heat transfer and thermal storage media for its low melting point and good thermal performance. In this paper, nanofluids were synthesized by dispersing MgO nanoparticles into LiNO3-NaNO3-KNO3, and the effects of nanoparticles on thermal properties were studied with different sizes (20–100 nm) and mass percent concentrations (0.5–2.0 wt.%). The addition of nanoparticles had little effect on melting temperature, and led to a slight increase in enthalpy of fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Nonlinear results revealed that the 20 nm and 40 nm MgO nanoparticles exhibited non-Newtonian behavior at weight concentrations higher than 5%. J. Lu et al [60] used molten salt LiNO 3 -NaNO 3 -KNO 3 with MgO nanoparticles to prepare nanofluid via a two-step technique. The synthesis technique was concluded by heating the mixture of molten salt and MgO nanoparticles to 350 • C and ultrasonication time for 1 h. The effect of nanoparticles on thermal properties was studied with different sizes ranges of 20-100 nm, weight concentrations from 0.5 to 2.0 wt.%, and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear results revealed that the 20 nm and 40 nm MgO nanoparticles exhibited non-Newtonian behavior at weight concentrations higher than 5%. J. Lu et al [60] used molten salt LiNO 3 -NaNO 3 -KNO 3 with MgO nanoparticles to prepare nanofluid via a two-step technique. The synthesis technique was concluded by heating the mixture of molten salt and MgO nanoparticles to 350 • C and ultrasonication time for 1 h. The effect of nanoparticles on thermal properties was studied with different sizes ranges of 20-100 nm, weight concentrations from 0.5 to 2.0 wt.%, and temperature.…”
Section: Introductionmentioning
confidence: 99%